2019
DOI: 10.1111/bdi.12782
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological effects of multiple mood episodes in bipolar disorder

Abstract: Objectives: Bipolar disorder is marked by progressive symptomatic changes, which have been linked with episode-related structural findings-particularly in the prefrontal cortex. However, few studies have examined neurofunctional and neurochemical effects of disease burden. In this study, we compared first-and multi-episode bipolar individuals. We hypothesized that the latter would demonstrate evidence of neurophysiological differences consistent with a model of progressive functional degradation of these netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…Furthermore, patients with multiple episodes potentially encounter progressive neuropathological changes when mood episodes relapse 32 , 33 . Previous studies have reported that neuropathological progression includes deactivation of fronto–limbic–striatal regions 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with multiple episodes potentially encounter progressive neuropathological changes when mood episodes relapse 32 , 33 . Previous studies have reported that neuropathological progression includes deactivation of fronto–limbic–striatal regions 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Estudios más recientes que evalúan el efecto de los episodios afectivos recurrentes compararon neuroimágenes funcionales de pacientes en su primer episodio con las de pacientes con múltiples episodios afectivos, y observaron que los pacientes con curso crónico y múltiples descompensaciones presentan menor activación en los tractos prefrontal -estriado -amigdalino y de forma bilateral en los talamos, las cortezas prefrontal ventro lateral, orbitofrontales y cingulada anterior, putamenes, caudados, amígdalas, área 22 de Brodmann y regiones parietales posteriores derecha. Es probable que alteraciones neurofisiológicas asociadas a un mayor número de episodios afectivos lleven a un decremento de la activación de redes neuronales implicadas en la regulación afectiva en pacientes con TAB (47), y a su vez tenga correlación teórica con alteraciones estructurales que pueden variar de acuerdo con la PP.…”
Section: Discussionunclassified
“…As mentioned before, this has a direct correlation with the alteration in the kynurenine pathway. However, the specific findings regarding Glx are mixed; although the most common finding is an increase in its concentration, some studies report a decrease, [ 27 ] or no changes at all [ 26 , 28 , 29 ]. This variation may be due to the region studied, to the different subgroups of BD studied, to an undetermined effect of the medication, or to the limited number of patients studied [ 26 ].…”
Section: Reviewmentioning
confidence: 99%